Chronic Hepatitis B Virus Infection in Children and Adolescents in Japan. Issue 1 (January 2015) - Komatsu, Haruki; Inui, Ayano; Sogo, Tsuyoshi; Tsunoda, Tomoyuki; Fujisawa, Tomoo
ABSTRACT: Background: Hepatitis B e antigen (HBeAg) seroconversion is an important event in patients with chronic hepatitis B virus (HBV) infection. This study aimed to clarify the outcome of long-term follow-up of chronic HBV infection and the factors affecting HBeAg seroconversion in children in Japan. Methods: Patients who were first examined at our institution between 1980 and 2012, who were <20 years of age at the time of this initial visit, and who were positive for hepatitis B surface antigen for at least 6 months were identified retrospectively. Sex, age at diagnosis, HBV genotype, maximum serum alanine aminotransferase (ALT) level, occurrence of hepatitis flare-ups (yes/no), and transmission route were evaluated to identify the predictors of HBeAg seroconversion. Results: A total of 205 children with chronic HBV were enrolled. Among them, 192 were positive for HBeAg upon diagnosis of chronic HBV infection. Out of this group, 95 (49%) achieved HBeAg seroconversion and 43 (21%) received treatment during the follow-up period. Only the maximum serum ALT level was significantly associated with the achievement of HBeAg seroconversion by multivariate analysis ( P  < 0.05). Kaplan-Meier analysis showed that the median times to HBeAg seroconversion (50% achievement of HBeAg seroconversion) of the treated and untreated children were 10.2 and 12.0 years, respectively. The cumulative proportion of HBeAg seroconversion was significantly higher in the treated children than in the untreated children ( P  = 0.02). Conclusions: A higher serum ALT level was a predictor for HBeAg seroconversion. Antiviral treatment could accelerate the achievement of HBeAg seroconversion in HBV-infected children.